PD-1 Inhibitors Plus Capecitabine as Maintenance Therapy for Advanced Intrahepatic Cholangiocarcinoma: A Case Report and Review of Literature - Wang, Zhihong; Zeng, Tianmei; Li, Yong; Zhang, Ding; Yuan, Zhengang; Huang, Mengli; Yang, Yuan; Zhou, Weiping (Frontiers in Immunology, 2021)
Intrahepatic cholangiocarcinoma (iCCA) is the second most common primary liver cancer with a poor prognosis. Recently, an immunotherapy strategy represented by programmed cell death 1 (PD-1) inhibitors has been applied to the systemic treatment of advanced iCCA. However, immunotherapy combined with chemotherapy as first-line maintenance therapy was rarely reported. Our report presented an advanced iCCA patient who had a dramatic response to the PD-1 inhibitor sintilimab combined with gemcitabine plus cisplatin as the first-line therapy and sintilimab combined with capecitabine as maintenance therapy, yielding an ongoing progression-free survival of 16 months.